The role of bilateral internal iliac artery ligation in obstetric practice - Vetcha, Likhita; Sivaranjani, B. S. V.; Madhavi, K. N.; Pemma, Sirisha; Potharaju, Jayanthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum hemorrhage remains a leading cause of maternal mortality globally, accounting for a significant percentage of obstetric emergencies. Bilateral internal iliac artery ligation (IIAL) is a surgical technique that has been advocated for controlling severe pelvic hemorrhage for over a century. The main aim of this study was to evaluate the effectiveness of IIAL in controlling intractable obstetric hemorrhage and to assess its impact on hysterectomy rates and maternal outcomes. Methods: A prospective observational study was conducted between June 2023 and June 2024 in a tertiary care center. Women presenting with massive PPH unresponsive to conservative management were considered for IIAL. All procedures were performed by a senior obstetrician and a urologist. Data on patient demographics, indications for IIAL, surgical details, and maternal outcomes were recorded and analyzed. Results: A total of 30 patients underwent IIAL, primarily for morbidly adherent placenta and uterine atony. Of these, 62.5% avoided hysterectomy following successful ligation, thereby preserving the uterus. There were no major surgical complications, and the need for excessive blood transfusions was markedly reduced after IIAL. Conclusions: IIAL is a valuable procedure in obstetric practice for managing life-threatening PPH, especially in resource-limited settings where advanced interventional radiology may not be readily available. By effectively reducing pelvic arterial pressure, IIAL can control hemorrhage and lower the need for hysterectomy, thereby preserving fertility. Familiarity with pelvic anatomy and prompt surgical intervention are essential for successful outcomes.